Preparation and Characterisation of Pani Nanofibres Using Ferric Chloride As Oxidant in Presence of Hcl - Ananth Vino, V. Jose; Saini, Rajkumar (International Journal of Psychosocial Rehabilitation, 2019)
To prepare polyaniline (PANI) nanofibers by using FeCl3·6H2O as the oxidant in the presence of inorganic acids HCl without any external template and to characterize it.